Analysis of Basic Principles for Sensor System Design Process Mobile Robots - Vyacheslav Lyashenko; Svitlana Sotnik (Journal La Multiapp, 2020)
This work considers general classification of SS, which is grouped according to their functional tasks and consists of three groups of devices, as result, an analysis is carried out and features that must be taken into account when designing such sensor systems are determined. The paper proposes a general principle for design of sensor systems of mobile robots, which differs in that an initial model is proposed, which will be one of key components for further design concept. General principles of sensory systems organization are proposed: sensitivity, modality, adaptation and speed.